2012
DOI: 10.1682/jrrd.2010.07.0129
|View full text |Cite
|
Sign up to set email alerts
|

Vergence in mild traumatic brain injury: A pilot study

Abstract: Abstract-Vergence dysfunction in individuals with mild traumatic brain injury (mTBI) may have a negative effect on quality of life, functional abilities, and rehabilitative progress. In this study, we used a range of dynamic and static objective and subjective measures of vergence to assess 21 adult patients with mTBI and nearwork symptoms. The results were compared with 10 control adult subjects. With respect to dynamic parameters, responses in those with mTBI were slowed, variable, and delayed. With respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 29 publications
(46 reference statements)
4
63
0
Order By: Relevance
“…This suggests improved convergence sustainability involving the slow vergence mechanism [63]. Our previous study in this area [41] found abnormal, reduced vergence adaptation in those with mTBI, which is also typically found in those without mTBI but with vergence-related dysfunction and correlated symptoms [68]. In contrast, the SS variability did not change markedly for divergence at the 1-m test distance.…”
Section: Training Effect On Vergence Dynamicsmentioning
confidence: 82%
See 4 more Smart Citations
“…This suggests improved convergence sustainability involving the slow vergence mechanism [63]. Our previous study in this area [41] found abnormal, reduced vergence adaptation in those with mTBI, which is also typically found in those without mTBI but with vergence-related dysfunction and correlated symptoms [68]. In contrast, the SS variability did not change markedly for divergence at the 1-m test distance.…”
Section: Training Effect On Vergence Dynamicsmentioning
confidence: 82%
“…More recently, a wide range of static and dynamic vergence parameters were tested in 21 visually symptomatic adult patients with mTBI (mean ±1 standard error of mean [SEM] age: 45.7 ± 3.1 yr), as related to nearwork, by the State University of New York (SUNY) acquired TBI research group [41]. Five static parameters were found to be significantly different and abnormal between the mTBI and the visually nondisabled groups: near point of convergence (NPC) break and recovery values were receded, positive fusional vergence (PFV) break and recovery values were reduced, and the stereoacuity threshold was elevated (presumably related to inaccurate vergence) in the group with mTBI [10].…”
Section: Laboratory Investigationsmentioning
confidence: 99%
See 3 more Smart Citations